Los derechos humanos y el riesgo que causa el agua contaminada del rio moche a los habitantes de Trujillo - González Luján, Rudy Edinson (2011)
The following investigation covers the study of the violation of the human rights about the health and the healthy environment of the inhabitants of Trujillo by the Peruvian government, due to the risk that causes the polluted water of the Moche river with mine tailings. The instruments used were: author site cards, surveys and websites. Several places of the Moche river in Trujillo, Otuzco, Julcan and Santiago de Chuco were visited in order to verify if the pollution implies risk. It has been confirmed that the hypothesis of ““the risk that causes the water of the Moche river, polluted with mine tailings, is according the Peruvian State a violation of the human rights about life, health and a healthy environment of the inhabitants of Trujillo, because it does not take the preventive measures to protect them in spite of having knowing and the duty imposed by the Instruments of human rights.” It is necessary, therefore, that the implicit protection against risks has to be legislated specifically to facilitate that any person understands that if the State unreasonably does not protect the human rights against risks, it will end up in violation of these rights.